Extrarenal Wilms Tumor in the Retroperitoneum: An Unusual Case Report and Review of Literature - Hemavathi Narayan; Sanghamitra Mukherjee; Jesmy Mary Varughese; Priya Dharmalingam; Geeta V. Patil Okaly (Indian Journal of Medical and Paediatric Oncology)
Extrarenal Wilms tumor (ERWT) is an exceptionally rare neoplasm. The definition of an ERWT requires that it to be located extrarenally with histological evidence. ERWT is a unique tumor, with few reports in the literature. Till date, there have been only 51 reported cases of retroperitoneal ERWT in the literature. ERWT is a challenging entity to diagnose, treat, and prognosticate. We present a case of a 4-year-old girl with complains of abdominal mass for past 1 month. Abdominal contrast-enhanced computed tomography scan revealed an extrarenal large solid mass in the retroperitoneum. Postsurgery histomorphology and immunohistochemistry confirmed the tumor as ERWT displaying favorable histology. This case highlights the importance of a precise histopathology diagnosis as well as clinical acumen regarding such rare cases. In atypical clinical presentation with inconclusive imaging findings, the diagnosis is based on histomorphology and immunohistochemistry. It also aids in giving this unusual tumor a clear perspective.